Catalisar o sensível: uma cartografia dos afetos no cárcere - Nogueira, Beatriz Machado Alves (2024)
This research was born and developed by nourishing a restless soil on the prisons of bodies and the instinctual energy of life. The dissertation was cultivated with a critical, artistic and philosophical basis for the question of otherness, of the image of the other. This image is created by a subject and insistently reworked based on the image of oneself and the relationship that one has created with this "other". Experiencing sharing with someone who has much to say, to free. Creating, with essayistic reports, after years of living with the theme of imprisonment, entering the bars of some Brazilian prisons, with time to return to the freedom of the body, together with my photographic production inside and outside the walls, makes one think about how this entire scenario is set up in our contemporary world inside and outside of prison. I immerse myself in an aesthetic creation of language and image as a political practice and collective existence. Next, I ask what are the active potentialities and what are the limits for a research that goes through the reports of experiences in prison and the creation of images in an environment of deprivation of liberty in overlapping or collages with scenes that call the paradox to thought: freedom, the unconscious imagery and nature in action. In this process, I perceive how the dynamics in the field of macrophysics and microphysics of violence (HAN, 2017) work, creating a game between the real and the fictional, as a critical form of violence that feeds on the biopolitical devices (FOUCAULT, 2014) that regulate the visualities of the violent experience and the imaginary that we create and disseminate from images, bodies and spaces in contexts of marginalization in contemporary times. Finally, I bring up the importance of affects in academic research and writing, since I was guided precisely by them, by the discomforts and paradoxes that research with prison raises. By remaining outside of my comfort zone for much of this journey, I come to understand that it is this state of affectation that gives me the strength to exercise the state of alterity necessary to sustain the practices and state of micropolitics necessary in contemporary times.